ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK REKLAME PADA DINAS PELAYANAN PAJAK DAERAH PROVINSI DKI JAKARTA - Dwi Ratnaningsih; Waluyo Waluyo (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2017)
Tax compliance is an important aspect to achieve maximum tax revenue target. This study aims to determine the relationship among variables Knowledge Taxpayer, Rates & Tax Base, Complexity of The Rules, Tax Fairness, Administration and Advertisement Tax Procedures , Quality of Tax Officer, Penalties, Inspection And Control of The Billboard with the compliance of advertisement tax to the Local Tax Department of DKI Jakarta. This research was conducted by questionnaire survey method. The population in this study is advertisement tax payer, the one who serving advertisement in Jakarta. The sampling technique is purposive sampling random sampling, which in this case is limited to a specific subject that can provide the desired information. A total of 100 samples was selected based on the selection of this sample. The data was processed by multiple regression method. The results of this study show that the variable Taxpayers Knowledge, Tax fairness, Sanctions and Investigation and Control Billboard positive effect on advertisement tax compliance on the Local Tax Department of DKI Jakarta. Rates and Tax Base, as well as the complexity of the Regulation have a negative effect on the advertisement tax compliance. While the service factors that Administration and Procedures and Officer quality does not affect the advertisement tax.